PALEMBANG EXPLORE APPLICATION USING ANDROID - Nyimas Sopiah; Redho Aidil Iqrom (Universitas Bina Darma, 2019)
This research produced an Palembang Exlore application which is an application for tourism promotion in Palembang City. Tourism here is not only historical sites, but also can be other tours, including historical or famous places / buildings in a city, where you can buy souvenirs or souvenirs, where to buy special foods from a region or culinary, and so on. This application is useful for tourists, both domestic and foreign who will visit the city of Palembang. So that tourists are expected to know all the tourist attractions that can be visited, ranging from tourist places or historic buildings to culinary tours of the city of Palembang. The method used in making this application or software uses the Extreme Programming method which consists of several stages, namely planning, design, coding and testing. The application is made using HTML 5 programming language. This application is used through the Android operating system